Critical success factors model for residential building maintenance in Libya - R Alriwaimi, Hani Muftah (2018)
Libya faces challenges in its effort to provide adequate maintenance for residential buildings. Presently, more maintenance work is required in order to cope with huge construction growth in Libya. However, the growth of maintenance industry is not expanding as it should. Despite government's best efforts to address this problem, little success has been recorded for maintenance of residential buildings. Literature attributed the low success rate due to issues such as no proper guidelines and enforcement on delay payment of maintenance work, poor customer service provided by property management organization, design deficiency and defects in residential unit, deferred maintenance and poor management. Maintenance of residential building is not only essential for the general well-being of individuals, but an effective implementation of building maintenance will promote socio-economic development of individuals and a nation. However, there is still lack of studies on critical success factors for residential building maintenance. Therefore, the aim of this research is to establish the critical success factors (CSFs) that influence the success of residential building maintenance in Libya. The data collection was ca1Tied out in Libya, and it included of expert judgment, pilot study and questionnaire survey. The expert judgment survey were conducted with experts in order to check the relevance of the variables identified from the literature review with respect to Libyan context, and to identify additional variables not listed in the questionnaire form. Based on the results of the expert judgment survey, the variables were modified and used in the development of questionnaire. A pilot survey was conducted to expose problems or weaknesses in the questions and to pre-test the clarity and comprehensibility of the questionnaire. A questionnaire survey was then conducted with a total of 350 questionnaires were administered by self-administered questionnaire survey to consultants, contractors, clients and those working in handling residential building maintenance. A total of 327 completed questionnaires were returned. The data collected were analyzed by means of Pa11ial Least Square technique based on Structural Equation Modeling (PLS-SEM), in order to test the relationship between CSFs and residential building maintenance success. The results established eight (8) factors which are critical to the success of residential building maintenance in Libya: project management factor, project participants factor, environment and site factor, health and safety factor, time factor, quality factor, financial factor, and other factors. The critical success factors established in this study can guide project managers and policy makers in the planning and implementation of adequate maintenance for residential buildings in Libya.